Sweet Snack Foods Are Promoted by the Baby Food Industry: A Survey of Baby Foods in the UK - Garcia, Ada (Curr Dev Nutr, 2020)
OBJECTIVES: Snacking is nor part of UK complementary feeding recommendations, but 60% of UK infants aged 7–10 months consume home-made and/or commercial baby snacks. We aimed to explore trends in the availability of commercial baby snacks in the UK food market over time. METHODS: We surveyed all infant food products available to buy in the UK, online and in-store, n 2019 and used our own 2010–2011 data for comparison. Product type [wet purees or dry (snacks)] were recorded at both time points. In 2019 for snack products we recorded main types, feeding claims on product packaging and sugar content. RESULTS: The total number of products available in 2010–11 and 2019 was 482 and 865 respectively. The proportion of snacks had doubled between 2010–11 (42, 10%; P = 0.001) and 2019 (185, 21%), while the proportion of wet, pureed foods decreased (2010–11 326, 79%; 2019 611, 71%; P = 0.001) and in 2019 were mainly supplied in pouches (453, 74%). The commonest snack types in 2019 were corn based flavoured with fruit or vegetables (40%; of which 12% fruit flavoured), dried fruit (15%), fruit or vegetables mixed with cereals (22% of which 88% were fruit based), biscuits (18%), and rice cakes flavoured with fruit or vegetables (8%). In 2019 front of package feeding claims were observed on 43% of snacks, referring to them as ‘finger foods’ (25%), ‘encourages self-feeding’ (10%), ‘perfect for teething’ (4%) or a mixture of these (3%). Sugar content [N, g/100 g median (Q1, Q3)] was higher than the 5 g/100 g recommended threshhold for all dried fruit [19, 61(38, 64], fruit or vegetable with cereals [42, 26(18, 29)], biscuits [34, 19(15, 22)] and rice cakes [34, 19(15, 22)]. Corn snacks [75, 4(2, 6)] mainly met the sugar content threshold. CONCLUSIONS: Sweet commercial baby snacks are a prominent feature of the UK food environment. Regulations on feeding claims and sugar content are urgently needed. FUNDING SOURCES: No funding sources to declare.